(untitled) (Education in the 21st Century, 2023)
The aim of the present research is to define the goals and targets, stages and specifics of implementation of STEM education in Armenian reality. The objective of the study is to reveal and to try to find solutions to the problems and restrictions, which arise within the system of STEM school and higher educational institutions. General scientific (logical) and specific (comparative and statistical) methods were used to carry out a comprehensive analysis. STEM education is an initiative to instruct competitive specialists in the era of technologies, and it will greatly contribute to professional education at university. STEM schooling can foster competitiveness to provide opportunities for learners to specialize in high technologies, and to become highly qualified IT specialists through realization of innovative ideas and developing high-tech products. Cooperation in science and innovative ideas provide effective solutions not only in educating and training specialists, but also in agriculture, ecology, sustainable energy, urban infrastructure, etc. STEM education opens perspectives for learners to easily find a job. While investigating the issue we came to the conclusion that STEM schooling is a challenge. Its successful realization will both boost the quality of education and science, and it will also contribute to raising citizens whose activities will improve social conditions and contribute to nation’s development and prosperity. Principles of STEM instruction have brought about certain restrictions, which can be solved applying new methods of teaching, technologies, and quality education. Yerevan State University STEM school was founded to achieve these goals.